A mind-reading puzzle: Autistic people are more efficient at a theory-of-mind task. (March 2023) - Loza, Estefania; Amsellem, Frédérique; Zalla, Tiziana; Cartigny, Ariane; Leboyer, Marion; Delorme, Richard; Ramus, Franck; Forgeot d′Arc, Baudouin
Abstract: Theory of Mind (ToM) is essential to adapt in social situations; however, a ToM deficit might be involved in autism. To better understand how ToM reasoning affects problem solving in autistic and non-autistic individuals, we compared autistic and non-autistic children and adults in a series of problems presented in social and non-social framings, using an adapted version of a classical referential communication task. In the social framing, participants were asked to anticipate the behavior of an agent who might ignore some components of the scene. In the non-social framing, the task required participants to consider and ignore similar features of the scene, but an agent was not involved. Simply framing the task as a social one increased the difficulty, particularly for non-autistic participants. Interestingly, the framing had less of an impact on autistic participants, who showed better performance in the social task relative to non-autistics and maintained similar performance across framings. We propose that autistic participants might have translated the social instructions into a general rule that proved more efficient in this situation. Our findings suggest a critical distinction between ToM understanding and the continuous use of a ToM strategy in repeated situations. Highlights: We studied how autistic individuals take someone else's perspective. An adapted referential communication task was used to assess theory-of-mind. Autistic participants outperformed controls in the social version of the task. Autistic participants might have translated the task requirements into a non-social rule. Results show how autistic strategy may enhance performance.